Successive failure, repeat entrepreneurship and no learning: A case study - Marius Pretorius (SA Journal of Human Resource Management, 2011)
Orientation: Current theories of repeat entrepreneurship provide little explanation for the effect of failure as a ‘trigger’ for creating successive ventures or learning from repeated failures. Research purpose: This study attempts to establish the role of previous failures on the ventures that follow them and to determine the process of learning from successive failures.